IMPELEMENTASI PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO.109 DI INISIATIF ZAKAT INDONESIA - Utami, Danita Astri; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2020)
This study discusses financial accouting standarss that must be used by Zakat Management Organizations (OPZ) as a from of transparency, and accountability to the public and government.The standards initiated by the Indonesian Accounting Association (IAI) namely, PSAK of number 109 concerning Zakat, Infaq/Alms. Accounting includes recognition and measurement, presentation and disclosure. In addition, it can increase the trust of muzaki to give their funds to official zakat institutions. One of them, namely the Inisiatif Zakat Indonesia (IZI) which has received the title of Fair without Exception in 2017. So, the research objective is obtained to determine the suitability of the application with PSAK of number 109. The research method used is qualitative. The regarding the stage analysis carried out by describing the treatment of recording the financial statements of the Inisiatif Zakat Indonesia (IZI) the compare it with PSAK of number 109. The results of this tudy concluded that the financial report made by Inisiatif Zakat Indonesia (IZI) were in accordance with PSAK of number 109.